2019
DOI: 10.1590/0037-8682-0357-2018
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the presence of triatomines in rural areas of south Argentine Chaco

Abstract: Introduction: The domestic and peridomestic presence of Triatoma infestans depends on several factors, such as human behavior, vector behavior, ecology, and the environment. Methods: This work was conducted in 139 domiciliary units, where triatomines were captured and risk factors in domiciles and peridomicilies were recorded. Household dwellers were interviewed to obtain information about practices regarding this disease and entomological indicators were calculated. Results: Infestation indices were 59.7% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Previous studies carried out in the same region, during 1962 and 1984, had reported three sylvatic species -T. breyeri, T. guasayana and T. eratirusyformis-, invading houses but without colonizing them [56]. A more recent study in the same area also reported the presence of T. guasayana and T. garciabesi in peridomicile structures [57].…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies carried out in the same region, during 1962 and 1984, had reported three sylvatic species -T. breyeri, T. guasayana and T. eratirusyformis-, invading houses but without colonizing them [56]. A more recent study in the same area also reported the presence of T. guasayana and T. garciabesi in peridomicile structures [57].…”
Section: Discussionmentioning
confidence: 86%
“…Entomological data recorded in this study shows high peridomestic infestation (43.9 %) and very low domestic infestation (1.5 %) by T. infestans in rural houses of the northwest of Córdoba Province during 2012-2013. Previous reports published within the same area, pointed out that low domestic infestation was related with the improvement of housing construction and that the risk of peridomestic infestation was strongly associated with the presence of chicken coops (Crocco et al 2019). Since rural houses were visited after a three year-period without chemical control, the levels of peridomestic infestation recorded supports the fact that without a sustainable control campaign the populations of T. infestans remain far from the elimination objectives proposed by the Southern Cone Initiative (Segura 2002).…”
Section: Discussionmentioning
confidence: 89%
“…The northwest region of Córdoba Province, located in the south of the Gran Chaco region of Argentina, shows a heterogeneous scenario of T. cruzi transmission related with differences in vector control interventions, land use changes and socioeconomic factors in the last decades (Moreno et al 2010(Moreno et al , 2012. Previous reports on the area (Crocco et al 2019), showed a high peridomiciliar infestation, strongly associated with the presence of chicken coops. This peridomestic habitat is the most frequent in the area and the most vulnerable to infestation because the materials of construction (sticks, wood, or cardboard) provide excellent refuge sites for triatomines.…”
Section: Introductionmentioning
confidence: 98%
“…Crocco et al [ 24 ] in their cross-sectional survey on risk factors associated with the presence of triatomines in rural areas of south Argentina report the following: Houses with unplastered walls had a 20.7 times greater risk of infestation ( p < 0.001) than those with uncracked plastered walls; similarly houses with unplastered concrete or brick, or thatched roofs had a 7.2 times greater risk of infestation than houses with plastered roofs ( p < 0.001). …”
Section: Results Of the Literature Review Concerning Housing Risk Fac...mentioning
confidence: 99%